The boy who followed Ripley - Highsmith, Patricia 1921-1995. (New York Vintage Books, 1993)
"In this quietly terrifying exploration of trust and friendship, a troubled young runaway arrives in Villeperce. And when, on the boy's behalf, Tom Ripley is drawn from his lovely estate in the French countryside to Berlin's seamy underworld and into a kidnapping plot that requires the most bizarre methods--and sinister acumen--for intervention, the icily amoral Ripley is transformed into a generous and compassionate protector."--Back cover.
Keywords: Ripley, Tom (Fictitious character) -- Fiction; Serial murderers -- Fiction; Psychopaths -- Fiction; Criminals -- Fiction; Fiction; Mystery fiction